2020
DOI: 10.3390/insects11060336
|View full text |Cite
|
Sign up to set email alerts
|

Enzymology, Histological and Ultrastructural Effects of Ar-Turmerone on Culex pipiens pallens Larvae

Abstract: Our previous article demonstrated that ar-turmerone ((6S)-2-methyl-6-(4-methylphenyl)-2-hepten-4-one) extracted from Curcuma longa L. has a significant larvicidal activity against the fourth instar larvae of Culex pipiens pallens. To reveal the effects of ar-turmerone on C. pipiens pallens larvae, light microscopy and transmission electron microscopy were used to observe the histological and ultrastructure changes in muscle and digestive tissues of fourth instar larvae. It was also revealed by detecting the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…39 The epithelial cells protruded in the midgut of Culex pipiens larvae, with the brush border entirely disorganized and thinning down after 24 h exposure with ar-turmerone (200 ppm). 45 Fiaz et al discovered, similarly to this work, that a damaged epithelial layer was associated with cell debris discharged in the midgut lumen, cytoplasm vacuolization followed by cell breakdown, and cell debris release into the midgut lumen. 46 The peritrophic membrane, also known as the peritrophic matrix (PM), is a non-cellular substance, a semi-permeable and fibrous layer created by midgut epithelial cell secretion, that separates the ingested food from the midgut epithelium.…”
Section: Discussionsupporting
confidence: 68%
“…39 The epithelial cells protruded in the midgut of Culex pipiens larvae, with the brush border entirely disorganized and thinning down after 24 h exposure with ar-turmerone (200 ppm). 45 Fiaz et al discovered, similarly to this work, that a damaged epithelial layer was associated with cell debris discharged in the midgut lumen, cytoplasm vacuolization followed by cell breakdown, and cell debris release into the midgut lumen. 46 The peritrophic membrane, also known as the peritrophic matrix (PM), is a non-cellular substance, a semi-permeable and fibrous layer created by midgut epithelial cell secretion, that separates the ingested food from the midgut epithelium.…”
Section: Discussionsupporting
confidence: 68%
“…caspius treated with Mentha rotundifolia (Kharoubi et al, 2020). Moreover, Liu et al (2020) showed that ar‐turmerone significantly increased the level of GST enzyme in Culex pipiens pallens larvae. It was shown, also, an induction of this detoxifying enzyme activity in Spodoptera litura after application of purified compounds of Alpinia galangal (Datta et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Detoxifying enzymes consisting of acetylcholinesterase (AChE), glutathione S transferase (GST), esterase, and cytochrome c oxidase (oxidase) have been applied to assess the susceptibility of mosquito species to different insecticides. They could also be applied to assess the susceptibility of mosquito larvae to insecticides ( Boyer et al., 2006 ; Liu et al., 2020 ). Thus, metabolic enzymes are an important tool to assess the susceptibility of mosquito larvae and adults to insecticides.…”
Section: Introductionmentioning
confidence: 99%